Lifestyle changes may be more important than drugs for mild hypertension. (15th February 2019) - Cook, Rob; Lamont, Tara; Martin, Rosie
The study: Sheppard JP, Stevens S, Stevens R, Martin U, Mant J, Hobbs R, McManus R. Benefits and harms of antihypertensive treatment in low-risk patients with mild hypertension. Published on 1 December 2018 JAMA Intern Med 2018;178:1626-34. This project was funded by a grant from the National Institute for Health Research (NIHR-RP-R2-12-O15) and the Medical Research Council (MRC) Strategic Skills Postdoctoral Fellowship. To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000713/lifestyle-changes-for-mild-hypertension-rather-than-drugs